Effectiveness of several nutritional sources on the virulence of Beauveria bassiana s.l. CEP147 against the planthopper Delphacodes kuscheli - Toledo, Andrea Vanesa (2022)
Delphacodes kuscheli Fennah (Hemiptera: Delphacidae) is the main planthopper vector of Mal de R ıo Cuarto virus (MRCV), a Fijivirus that severely affects maize production in Argentina. The effect of several nutritional sources on the virulence of Beauveria bassiana s.l. CEP147 (Balsamo-Crivelli) Vuillemin (Hypocreales: Cordycipitaceae) against this planthopper was evaluated with the aim to select some of them to be incorporated in future mass production studies. Ten agar-agar 2% media were used. Media were supplemented with 10 g of sucrose and 4% flour of either amaranth, chia, flax, oat bran, parboiled rice, poppy, quinoa, or wheat germ. Sabouraud dextrose agar with 1% yeast extract (SDAY) was used as control, and sucrose agar medium supplemented with 2% chitin was used as a possible inductor of enzymatic activity. We evaluated the effect of each medium on colony growth, conidial yield, viability, size, adherence, hydrophobicity, protease activity, cumulative mortality, and median survival time (MST). Principal component analysis indicated that conidial viability and adherence explained the most of the total variance, indicating that these variables can be used as indicators of fungal virulence. Medium supplemented with chia flour not only increased conidial viability (100%) and adherence (0.09 A550) with respect to the control medium, but also produced high D. kuscheli mortality (91.7%), with the lowest MST (5.2 days).We suggest that chia flour, which is rich in carbohydrates, proteins, vitamins, andminerals, might be incorporated as a nutritional supplement to solid substrates in order to increase the virulence of B. bassiana s.l. CEP147 against this and other pests. However, future studies are necessary to evaluate the effectiveness of this nutritional source on solid-state fermentation.